A comparative study of the oxidation of dopamine in deep eutectic solvents: A potential approach to synthesis polydopamine particles with various shapes, sizes, and compositions. Issue 18 (28th December 2021) - Shiraz, Mina Ghasempour; Absalan, Ghodratollah; Tashkhourian, Javad
Abstract: In a comparative study, polymerization of dopamine in choline chloride/ethylene glycol (ChCl/EG) as well as ZnCl2 /ethylene glycol (ZnCl2 /EG), as the deep eutectic solvents (DESs), has been individually studied. To do this, copper sulfate (CS), ammonium peroxydisulfate (AP), and sodium periodate (SP), as the individual oxidants, were also investigated. It is demonstrated that DESs have the potential of being utilized in the preparation of stable suspensions of polydopamine (PDA) particles with various shapes including porous capsules, spongy, and flower‐like structures. It is also shown that the morphology and composition of the produced PDA particles were strongly affected by the chosen DES, the oxidant, and the polymerization time, which can allow a one‐pot synthesis and modification procedure for producing PDA with desired functionality. Abstract : A one‐pot synthesis and modification procedure for producing polydopamine (PDA) particles with desired functionality was suggested by investigating the oxidation of dopamine in two deep eutectic solvents (DESs) in the presence of three different oxidants. The results showed that DESs have the potential of being utilized in the preparation of stable suspensions of PDA particles with various shapes, sizes, and compositions.